Nitric Oxide Synthase Inhibitor Improves De Novo and Long-Term l-DOPA-Induced Dyskinesia in Hemiparkinsonian Rats - Padovan-Neto, Fernando E.; Echeverry, Marcela B.; Chiavegatto, Silvana; Del Bel, Elaine (Frontiers in Systems Neuroscience, 2011)
Inhibitors of neuronal and endothelial nitric oxide synthase decrease l-3,4-dihidroxifenilalanine (l-DOPA)-induced dyskinesias in rodents. The mechanism of nitric oxide inhibitor action is unknown. The aims of the present study were to investigate the decrease of l-DOPA-induced abnormal involuntary movements (AIMs) in 6-hydroxydopamine (6-OHDA)-lesioned rats by nitric oxide inhibitors following either acute or chronic treatment. The primary findings of this study were that NG-nitro-l-Arginine, an inhibitor of endothelial and neuronal nitric oxide synthase, attenuated AIMs induced by chronic and acute l-DOPA. In contrast, rotational behavior was attenuated only after chronic l-DOPA. The 6-OHDA lesion and the l-DOPA treatment induced a bilateral increase (1.5 times) in the neuronal nitric oxide synthase (nNOS) protein and nNOS mRNA in the striatum and in the frontal cortex. There was a parallel increase, bilaterally, of the FosB/ΔFosB, primarily in the ipsilateral striatum. The exception was in the contralateral striatum and the ipsilateral frontal cortex, where chronic l-DOPA treatment induced an increase of approximately 10 times the nNOS mRNA. Our results provided further evidence of an anti-dyskinetic effect of NOS inhibitor. The effect appeared under l-DOPA acute and chronic treatment. The l-DOPA treatment also revealed an over-expression of the neuronal NOS in the frontal cortex and striatum. Our results corroborated findings that l-DOPA-induced rotation differs between acute and chronic treatment. The effect of the NOS inhibitor conceivably relied on the l-DOPA structural modifications in the Parkinsonian brain. Taken together, these data provided a rationale for further evaluation of NOS inhibitors in the treatment of l-DOPA-induced dyskinesia.